Kehidupan Sosial Ekonomi Petani Jagung Di Nagari Geragahan Kampung Tabuah Kecamatan Lubuk Basung Kabupaten Agam Tahun 2007-2020 - Nofriya Nofriya; Azmi Fitrisia (Jurusan Sejarah FIS UNP, 2022)
Abstract This study examines the socio-economic life of corn farmers in Nagari Geragahan, Tabuah Village, Lubuk Basung District, Agam Regency, 2007-2020. The problems are formulated as follows: